¿CÓMO PERCIBEN LAS INSTITUCIONESPÚBLICAS Y PRIVADAS A LAS UNIVERSIDADES EN EL FOMENTO DEL EMPRENDIMIENTO? - Pérez Palacios, Emma Emilia (2011)
This paper presents the second part of the study results “Promoting Entrepreneurship in the University Youth 2010” This study reflects the inputs of 9 higher education establishments and 5 public and private institutions linked to the promotion of entrepreneurship. This time we present the position of scholars and practitioners in the promotion of entrepreneurship of public and private institutions regarding the role of universities in this noble work. Based on this study, encourage entrepreneurship is important in the process of training of university students, despite this classification, the public and private institutions believe that higher education institutions are not seeing in promoting entrepreneurship a valid path for the realization professional staff and youth.